Pengaruh Gaya Kepemimpinan Kepala Desa Terhadap Motivasi Kerja Perangkat Desa di Desa Lendang Nangka Kecamatan Masbagik Kabupaten Lombok Timur - Nova Hari Santhi; Silvia Harmiatun; Hartiani Hartiani (Pusat Riset dan Inovasi Nasional, 2024)
Leadership style is a method used by leaders to interact with their subordinates. Work motivation is the encouragement to direct subordinates to work productively to realize the goals that have been set. This research aims to determine and analyze the influence of the village head's leadership style on the work motivation of village officials in Lendang Nangka Village, Masbagik District, East Lombok Regency. This research is a type of quantitative descriptive research, namely research that describes research variables using a quantitative approach, namely research in which the population in this research is the Lendang Nangka Village Apparatus of 20 people. The sample in this study used a non-probability saturated sampling technique. The sample in this study was 20 people. Data collection uses a questionnaire method. The questionnaire method was used to obtain respondents' responses regarding the Leadership Style variable and Work Motivation variable. The data analysis used to test the hypothesis in this research was using Simple Linear Regression analysis contained in the SPSS v.20 program. The results of this research are that the Village Head's Leadership Style significantly influences the Work Motivation of Village Officials with a positive coefficient, which explains that there is a directly proportional relationship between the two variables. With a Regression Coefficient for the Leadership Style Variable (X) of 0.417 with a sig value of 0.001, it illustrates that the Village Head's Leadership Style has a positive and significant influence on the Work Motivation of Village Officials, meaning that by implementing a good Village Head Leadership Style it will increase the work motivation of village officials in working. , so that the performance of village officials increases.